2021
DOI: 10.5812/ijpbs.113164
|View full text |Cite
|
Sign up to set email alerts
|

Persian Version of Social Appearance Anxiety Scale: A Psychometric Evaluation

Abstract: Background: Social appearance anxiety refers to the fear of negative evaluation and judgment about appearance in social situations. Previous scales have focused more on body dysmorphic, and a tool that can measure this anxiety in social situations has not been previously introduced. Objectives: This study aimed to investigate the factor structure and psychometric properties of the Social Appearance Anxiety Scale (SAAS) in the student community. Methods: This psychometric study was conducted on a sample of 415 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The SAAS in our study have demonstrated good internal consistency with Cronbach’s alpha= 0,942, which is consistent with the results of the initial research of Hart et al . (2008) (a1 = 0.94, a2 = 0.95, a3 = 0.94 for the 3 samples) and with validations in other languages ( Reichenberger et al ., 2021 ; Doğan, 2010 ; Goodarzi et al ., 2021 ; Donofre et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SAAS in our study have demonstrated good internal consistency with Cronbach’s alpha= 0,942, which is consistent with the results of the initial research of Hart et al . (2008) (a1 = 0.94, a2 = 0.95, a3 = 0.94 for the 3 samples) and with validations in other languages ( Reichenberger et al ., 2021 ; Doğan, 2010 ; Goodarzi et al ., 2021 ; Donofre et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…al., 2008 ) and this finding was consistent with other studies in which participants’ SAAS scores did not differ considerably according to sex ( Amil and Bozgeyikli, 2015 ; Şahin et al ., 2013 ). In line with other studies, SAAS demonstrated a significant positive correlation with SPAS ( Hart et al ., 2008 ; Goodarzi et al ., 2021 ). Additionally, in our study SAAS was positive correlated with measures such as overweight preoccupation, and negative correlated with the appearance evaluation, which is consistent with the results of another validation of the scale ( Reichenberg et al ., 2021 ) and the original study ( Hart et al ., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation